Использование защищенной почты для ДО - Горбенко, И. Д.; Качко, Е. Г.; Марченко, С. Ю.; Дягилева, Ф. Г. (УАДО, 2002)
The questions of the protected mail use for remote education are considered. The application of the digital signature will ensure integrity, authenticity and participation for all documents of the email. The digital signature law on the will give legal force to the documents
Keywords: дистанционное обучение; образование